2019
DOI: 10.1039/c9sc02870f
|View full text |Cite
|
Sign up to set email alerts
|

Installation of internal electric fields by non-redox active cations in transition metal complexes

Abstract: Experimental and computational study quantifying internal electric fields in synthetic systems using transition metal Schiff base complexes functionalized with a crown ether unit containing a mono- or dicationic alkali or alkaline earth metal ion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
72
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(86 citation statements)
references
References 47 publications
(48 reference statements)
2
72
1
Order By: Relevance
“…Electric fields are known to play an important role in many catalytic transformations throughout chemistry 1 20 and biology. 21 , 22 For example, in molecular catalysis, charged moieties in the secondary sphere of a coordination compound can impart oriented internal electric fields, 11 , 13 15 which have been used to accelerate CO 2 activation ( Figure 1 , left). 11 Similarly, in enzymes, amino acid residues sustain enormous oriented electric fields within the active site that can drive biological catalysis ( Figure 1 , center).…”
Section: Introductionmentioning
confidence: 99%
“…Electric fields are known to play an important role in many catalytic transformations throughout chemistry 1 20 and biology. 21 , 22 For example, in molecular catalysis, charged moieties in the secondary sphere of a coordination compound can impart oriented internal electric fields, 11 , 13 15 which have been used to accelerate CO 2 activation ( Figure 1 , left). 11 Similarly, in enzymes, amino acid residues sustain enormous oriented electric fields within the active site that can drive biological catalysis ( Figure 1 , center).…”
Section: Introductionmentioning
confidence: 99%
“…In homogeneous chemistry, the electrostatic field of certain cationic species can impact the redox behavior of dissolved molecular complexes. 114 Interfacial chemistry in heterogeneous systems is commonly modulated by ionic additives 115 117 and electrolyte ions 118 120 in various electrocatalytic processes. Such strategies can be extrapolated to framework materials.…”
Section: Discussionmentioning
confidence: 99%
“…Non-redox active cations of varying charge are easily inserted into the crown cavity which significantly modifies the electric field potential around the redox active metal. 51 Our previous investigation of Mn(V) salen nitrido complexes (1-Na, 1-K, 1-Ba, 1-Sr) with bound alkali and alkaline earth metals showed that an increase of cationic charge at the complexes resulted in anodic shifts of over 400 mV of the Mn(VI/V) reduction potential (Table 1). 52 To expand on these studies, we synthesized two derivatives with +3 cations, so that our data set spans four different units of charge.…”
mentioning
confidence: 92%